2019
DOI: 10.1523/eneuro.0036-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-Induced Reduction in HCN Channel Expression Contributes to an Increased Excitability in Dorsal, But Not Ventral, Hippocampal CA1 Neurons

Abstract: CA1 neurons in epileptic animals are vulnerable to selective changes in ion channel expression, called acquired channelopathies, which can increase the excitability of a neuron. Under normal conditions there is a gradient of ion channel expression and intrinsic excitability along the longitudinal, dorsoventral axis of hippocampal area CA1 of the rodent. Many of these channels, including M-channels, GIRK channels and HCN channels, all have dorsoventral expression gradients that might be altered in rodent models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 80 publications
3
26
1
Order By: Relevance
“…The hexokinase has a lower affinity for ATP (Km=0.1-0.7mM 74 ) than the Na + /K + ATP-ase (Kd=0.1-0.2 µM 75 ), which could direct ATP to the pump rather than to the hexokinase, resulting in a decreased glucose uptake. Increases in glucose were more often observed in dorsal (7 from 9) than in ventral slices (3 from 9), which is consistent with the increased excitability of dorsal CA1 pyramidal cells in the pilocarpine model 76 .…”
Section: Metabolic Activity In Slices Of Dorsal and Ventral Hippocampsupporting
confidence: 78%
“…The hexokinase has a lower affinity for ATP (Km=0.1-0.7mM 74 ) than the Na + /K + ATP-ase (Kd=0.1-0.2 µM 75 ), which could direct ATP to the pump rather than to the hexokinase, resulting in a decreased glucose uptake. Increases in glucose were more often observed in dorsal (7 from 9) than in ventral slices (3 from 9), which is consistent with the increased excitability of dorsal CA1 pyramidal cells in the pilocarpine model 76 .…”
Section: Metabolic Activity In Slices Of Dorsal and Ventral Hippocampsupporting
confidence: 78%
“…Disorders characterized by alterations in neuronal excitability might have underlying dysregulation in the expression of HCN channels and associated proteins mediated by altered methylation. This mechanism is certainly possible for ASDs 16 but may be valid in other disorders, such as anxiety 43,44 , depression 14 , and epilepsy 45 . Second, interventions or manipulations that rely on broad spectrum or even isoform-specific modulation of PRMT7 function will affect neuronal excitability in CA1.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy HCN channels and TRIP8b have been implicated in several epilepsy subtypes including temporal lobe epilepsy (TLE) and absence epilepsy [83][84][85][86][87]. Animal models of TLE have consistently demonstrated reduced I h , hyperpolarization of channel activation, and mislocalization of HCN channels within CA1 pyramidal cells [88][89][90][91]. These changes likely increase the propensity of the network to spontaneous seizures as loss of HCN channel function within the CA1 has been linked to increased neuronal excitability, seizure susceptibility, and seizure-related death [7,77,92,93,94].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…The exact mechanisms by which HCN1 channel function is lost in the distal dendrites of CA1 pyramidal cells in TLE are unknown. Studies have either reported a global loss of HCN1 expression [90,91,95] or a loss specifically in the distal dendrites that correlates with reduced TRIP8b interaction [89]. Some authors have attributed the loss of HCN1 protein to transcriptional repression [90,96] while others cite posttranslational modifications of HCN channels and TRIP8b [54,97].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%